Oil and Civil Conflict : Can Public Spending Have a Mitigation Effect? - Singh, Raju Jan; Bodea, Cristina; Higashijima, Masaaki (World Bank Group, Washington, DC, 2014)
This paper explores the conditions under which public spending could minimize violent conflict related to oil wealth. Previous work suggests that oil can lead to violent conflict because it increases the value of the state as a prize or because it undermines the state's bureaucratic penetration. Yet, little has been said on how oil wealth could be used to prevent the onset of violent conflict through public spending by buying off citizens and elites, increasing state legitimacy by providing basic services, or strengthening the military and security apparatus. The empirical analysis (148 countries over 1960-2009) shows that higher levels of military spending are associated with lower risk of small- and large-scale conflict onset in countries rich in oil and gas. By contrast, in economies with little natural resources, increases in military spending are associated with a higher risk of conflict. Welfare expenditure is associated with lower risk of small-scale conflict, irrespective of the level of oil revenue. However, general government spending does not appear to have any robust mitigating effects.